Nutritional composition, bioactive compounds and antioxidant capacity of wild melon chunks as affected by different drying methods and storage - KAUR, PRABHDEEP; KAUR, HARPREET; BAINS, KIRAN; KAUR, SEHAJVEER (The Indian Journal of Agricultural Sciences, 2025)
Underutilised plants contribute significantly to food security and function as a means of existence. Wild melon commonly called kachri/chibbad is a member of the Cucurbitaceae family. The experiment was conducted during 2021–22 at College of Community Science, Punjab Agricultural University, Ludhiana, Punjab to evaluate the effect of different drying methods and storage conditions on biochemical parameters of wild melon chunks. The results showed that flavonoids (223.61 mg QE/100 g), alkaloids (51.53 mg/100 g) and antioxidant activity (DPPH- 66.19% and ABTS- 64.40%) in shade dried chunks were significantly (P≤0.05) higher than the oven dried chunks. Although the total phenols (451.34 mg GAE/100 g) and ascorbic acid (77.75 mg/100 g) content of shade dried chunks was higher than the oven dried, but there was no significant difference seen. There was significant (P≤0.05) decrease in the total phenols, flavonoids and antioxidant activity upon storage (3 months) and per cent retention of corresponding parameters was higher in shade dried as compared to oven dried chunks. In conclusion, wild melon may be a useful tool for promoting health, because it is a good source of phytonutrients and also drying could be a sustainable solution to reduce post-harvest losses and promote the utilization of wild melon as a functional food ingredient.